The effects of China's Organic-Substitute-Chemical-Fertilizer (OSCF) policy on greenhouse vegetable farmers. (15th May 2021) - Yi, Xiaoyan; Yu, Lerong; Chang, Sheng-Han-Erin; Yin, Changbin; Wang, Heng; Zhang, Zongfang
Abstract: For the sake of reducing the application of chemical fertilizers (CF) and achieve the goal of Zero Growth of CF until 2020, Chinese government released the "Action Plan for Organic-Substitute-Chemical-Fertilizer (OSCF) for Fruits, Vegetables and Tea" and initially performed it in 100 pilot counties from 2017. Each pilot county rewarded 10 million CNY as subsidy to substitute CF with organic fertilizers (OF). This study examines the effects of the OSCF policy using survey data of 281 greenhouse vegetable farmers in the Shandong province of China. The Difference-in-Difference (DID) method is employed to get the net effects of the policy on the utilization of replacing CF. The results show that the OSCF policy helps to significantly reduce the application of CF and increase OF's utilization for vegetable farmers, and on average CF drops 111.5 kg/ha while OF increases 346.36 kg/ha for the sampling farmers. Additional analysis reveals that the effects of the policy are heterogeneous across the cost of CF and household-level characteristics. The results provide evidences for further enhancing the policy effects. Highlights: Chinese government released the "Action Plan for Organic-Substitute-Chemical-Fertilizer (OSCF) for Fruits, Vegetables and Tea" and initially performed it in 100 pilot counties from 2017. This study examines the effects of the OSCF policy using survey data of 281 greenhouse vegetable farmers in the Shandong province of China. The Difference-in-Difference (DID) method is employed to get the net effects of the policy on the utilization of organic fertilizers replacing chemical fertilizers. The results show that the OSCF policy helps to significantly reduce the application of CF and increase OF's utilization for vegetable farmers, and on average CF drops 111.5 kg/ha while OF increases 346.36 kg/ha for the sampling farmers.